2013
DOI: 10.1097/meg.0b013e32835eb8bf
|View full text |Cite
|
Sign up to set email alerts
|

Durability of a sustained virological response, late clinical sequelae, and long-term changes in aspartate aminotransferase to the platelet ratio index after successful treatment with peginterferon/ribavirin for chronic hepatitis C

Abstract: The long-term outcome, including APRI, of chronic hepatitis C patients treated successfully with PegIFN/ribavirin and followed for a mean of 5.7 years is favorable. However, a high risk of progression to HCC and liver-related death remains for patients with pretreatment cirrhosis, in our setting, as high as 22.2 and 11.1%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…We observed that patients who attained SVR exhibited significant improvements in each of these markers after treatment. These results were consistent with previous studies showing similar results for surrogate markers . These improvements remained significant even when patients were grouped according to their baseline Metavir score (F0–F1, F2 and F3–F4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that patients who attained SVR exhibited significant improvements in each of these markers after treatment. These results were consistent with previous studies showing similar results for surrogate markers . These improvements remained significant even when patients were grouped according to their baseline Metavir score (F0–F1, F2 and F3–F4).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of patients successfully treated with interferon/ribavirin regimens have shown improvements in liver fibrosis after successful treatment using noninvasive blood biomarker tests . Here, we quantified how liver fibrosis improves in a large population ( N = 1208 patients) treated with antiviral regimens combining PR with the direct‐acting antiviral telaprevir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] In our study AST, ALT, AFP also decreased, which is consistent to other studies. 18,32,33 Compared to baseline we found significant increase in albumin values (p˂0.01), which is also proved in the study by Deterding et al, albumin levels became normal in most of his patients. 30 We found significant decrease in bilirubin levels at end of treatment (p˂0.01), which is desirable in hepatic patients.…”
Section: Discussionsupporting
confidence: 89%
“…Although, SVR would be regarded as a sign of clinical cure and with reduced risk of HCC for patients with SVR, HCC might be unavoidable to all patients with CHC. A previous study results suggested that patients with CHC who had no evidence of virological relapse might still have the risk of HCC ( 27 ). The mechanism of HCC development in patients with SVR is elusive.…”
Section: Discussionmentioning
confidence: 99%